The poetic of Akhmed Mitkhat Efendi the Turkish prosaic of the XIX centuries - Abeldaev, Zh. А. (Journal of Oriental Studies, 2016)
In this article is considered the problem of the Turkish prose which based on the works of the famous Turkish writer Ahmet Mithat Effendi in XIX centuries.